2001
DOI: 10.1021/bi0115380
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Binding to Pig Muscle 3-Phosphoglycerate Kinase in the Crystal and in Solution:  Relationship between Substrate Antagonism and Interdomain Communication

Abstract: Binding constants for the nucleotide substrates were determined in two different crystalline forms of pig muscle 3-phosphoglycerate kinase (PGK): the binary complex with 3-phosphoglycerate (3-PG) in which the two domains are in an open conformation (Harlos, Vas, and Blake (1992) Proteins, 12, 133-144) and the ternary complex with 3-PG and the Mg salt of the ATP analogue, beta,gamma-methyleneadenosine-5'-triphosphate (AMP-PCP), the structure of which is under resolution. Competitive titrations have been perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
31
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 29 publications
5
31
0
Order By: Relevance
“…Thus, our current understanding of ATP-synthesizing enzymes is still rudimentary at the molecular level and the key reaction responsible for the formation of the energy-carrying chemical bond POOOP remains obscure. Indeed, the structures of the protein parts and catalytic sites of phosphorylating enzymes, such as ATP synthase, creatine kinase, and phosphoglycerate kinase (PGK) (2)(3)(4)(5)(6)(7)(8)(9)(10), are well known. There is an understanding of their functioning as molecular rotary motors (referring to ATP synthase) or molecular pumps (creatine kinase, for instance); however, within the area of enzymatic reaction chemistry, all ideas are limited to speculations circulating mostly around nucleophilic mechanisms.…”
mentioning
confidence: 99%
“…Thus, our current understanding of ATP-synthesizing enzymes is still rudimentary at the molecular level and the key reaction responsible for the formation of the energy-carrying chemical bond POOOP remains obscure. Indeed, the structures of the protein parts and catalytic sites of phosphorylating enzymes, such as ATP synthase, creatine kinase, and phosphoglycerate kinase (PGK) (2)(3)(4)(5)(6)(7)(8)(9)(10), are well known. There is an understanding of their functioning as molecular rotary motors (referring to ATP synthase) or molecular pumps (creatine kinase, for instance); however, within the area of enzymatic reaction chemistry, all ideas are limited to speculations circulating mostly around nucleophilic mechanisms.…”
mentioning
confidence: 99%
“…This disturbs the coordination of the metal ion and its linkage with ␣-, ␤-, and ␥-phosphates and results in interaction of metal ion with Asp 375 and ␣-and ␤-phosphates. This leads to the collapse of the transition state to form metal-ADP and 1,3-biphosphoglycerate complexes bound to PGK, which then reverses the conformational change and releases the products (27)(28)(29). As with any reversible enzyme it is generally assumed that the phosphorylation of ADP to ATP using 1,3-biphosphoglycerate as a phosphate donor would also go through a similar transitional state (ED* ϭ EP*).…”
mentioning
confidence: 99%
“…This effect is called substrate antagonism. [2][3][4] With the phosphotransferase group of enzymes, both substrate synergy and substrate antagonism have been observed. For example, yeast hexokinase 5 and rabbit muscle creatine kinase 6 are subject to substrate synergy, whereas phosphofructokinase from Escherichia coli, 2,7 Rho-associated protein kinase (ROCK I; an enzyme that is implicated in cell adhesion and smooth muscle adhesion), 8 and, in particular, 3-phosphoglycerate kinase (PGK; EC 2.7.2.3) 9,10 are subject to substrate antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, Cliff et al reported a closed structure of hPGK. 11 High-resolution structures of the transition-state analogue complexes PGK·PG·MgF 3 − ·ADP and PGK·PG·AlF 4 − ·ADP, where metal fluorides replace the transferable phosphate of ATP, were obtained. It was suggested that a zero local net charge at the active site is a key feature of the phosphotransfer process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation